2014
DOI: 10.1002/em.21849
|View full text |Cite
|
Sign up to set email alerts
|

Time in hemodialysis modulates the levels of genetic damage in hemodialysis patients

Abstract: It is assumed that hemodialysis treatment can diminish the levels of genetic damage in circulating lymphocytes by cleaning the blood of uremic toxins that cause oxidative stress. However, the hemodialysis process by itself may also induce genomic damage by producing reactive oxygen species (ROS). We conducted a follow-up study in a group of 70 hemodialysis patients followed for a mean time of 15 months. We investigated the effect of exposure time in hemodialysis on the levels of genetic damage in peripheral bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Blood samples from heparinized vacutainers were processed as described previously using cytochalasin‐B to arrest cytokinesis [Rodríguez‐Ribera et al, ]. Two of the four cultures setup were irradiated with 0.5 Gy 137 Cs gamma rays in an irradiator IBL 437C, type H, No.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples from heparinized vacutainers were processed as described previously using cytochalasin‐B to arrest cytokinesis [Rodríguez‐Ribera et al, ]. Two of the four cultures setup were irradiated with 0.5 Gy 137 Cs gamma rays in an irradiator IBL 437C, type H, No.…”
Section: Methodsmentioning
confidence: 99%
“…Th e usefulness of the MN assay to evaluate individual ionizing radiation sensitivity has been reported to determine the intrinsic sensitivity to ionizing radiation in cancer patients, as well as in human immunodefi ciency virus (HIV)-positive individuals (Baeyens et al 2002, Mozdarani et al 2005, Christiakov et al 2008, Vral et al 2011, Bhatia and Kumar 2013. In addition, the frequency of BNMN has also been used to determine that CKD patients presented higher levels of MN than controls (Fragedaki et al 2005, Kobras et al 2006, Schupp et al 2008a, 2008b, Stopper et al 2008, Demircigil et al 2011, Rangel-L ó pez et al 2013, Rodr í guez-Ribera et al 2014. Th is would confi rm the usefulness of the MN assay in genomic instability studies and in the detection of the tendency that CKD patients had to present high levels of genomic damage.…”
Section: Declaration Of Interestmentioning
confidence: 97%
“…This increased cancer risk is independent of symptom severity or whether they are undergoing dialysis. Previous studies have demonstrated increased levels of DNA damage and genomic instability in CKD patients (Sandoval et al, , 2012Stoyanova et al, 2010Stoyanova et al, , 2014Rodr ıguez-Ribera et al, 2014). This damage can be directly related with the high incidence of cancer and/or mortality in patients.…”
Section: Introductionmentioning
confidence: 95%
“…The micronucleus assay was set up as previously described (Rodr ıguez-Ribera et al, 2014). The micronucleus assay was set up as previously described (Rodr ıguez-Ribera et al, 2014).…”
Section: Lymphocyte Culture and Micronucleus Assaymentioning
confidence: 99%
See 1 more Smart Citation